Efficacy and cost-effectiveness analysis of 10-day versus 14-day eradication of Helicobacter pylori infection with vonoprazan amoxicillin: a prospective, multicenter, randomized controlled trial - Yunfan Dong; Zhaotao Duan; Min Liu; Yanbing Ding; Guangxia Chen; Ruifang Wang; Xiaodan Xu; Lixia Ding; Qiang Zhan; Chengyu Pan; Hui Li; Faming Yang; et al. (Frontiers in Pharmacology)
ObjectivesTo evaluate the efficacy and cost-effectiveness of 10-day vonoprazan-amoxicillin (VA) dual therapy compared to 14-day VA therapy.MethodsA non-inferiority trial was carried out at 10 clinical centers to recruit patients with H. pylori infection. Subjects were assigned at random to either the group for 10-day or 14-day, and where given vonoprazan 20 mg bid and amoxicillin 1 g tid. Comparisons were made in terms of eradication rates, adverse events, cost-effectiveness, and compliance.Results914 participants were enrolled and randomly assigned to either the 10-day or 14-day VA groups. Using the intention-to-treat principle and multiple imputation for missing outcomes, the analysis showed an eradication rate of 88.79% in the 10-day group and 92.37% in the 14-day group (P = 0.064). The eradication rates were 89.14% and 93.35% by per-protocol analysis (P = 0.037). There were no significant differences in adverse events or compliance between the groups (P > 0.05). Logistic regression analysis indicated that smoking and prior failure of eradication were risk factors influencing the eradication rate (P < 0.05). For the economic evaluation, the cost-effectiveness ratio (CER) of the 10-day group was 426.30 yuan, the CER of the 14-day group was 485.27 yuan, and the incremental cost-effectiveness ratio was 1680.23 yuan. In probability sensitivity analysis, the cost-effectiveness acceptability curve showed that when the willingness-to-pay(WTP) threshold was below 1742 yuan, the 10-day group was more cost-effective. When the WTP threshold was above 1742 yuan, the 14-day group was more cost-effective.ConclusionIn this study, the 10-day VA was not found to be inferior to the 14-day VA. Compared with the 14-day group, the 10-day group is more cost-effective, but as the WTP threshold increases to 1742 yuan, the probability of the 14-day group being more cost-effective was greater than that of the 10-day group. Smoking and previous eradication attempts were associated with the eradication failure of VA therapy.Clinical Trial Registrationhttps://clinicaltrials.gov/, identifier NCT05469685.